Low dose of alcohol attenuates pro-atherosclerotic activity of thrombin. (October 2017) - Toda, Masaaki; Totoki, Toshiaki; Nakamura, Chizu; Yasuma, Taro; D' Alessandro-Gabazza, Corina N.; Mifuji-Moroka, Rumi; Nishihama, Kota; Iwasa, Motoh; Horiki, Noriyuki; Gabazza, Esteban C.; Takei, Yoshiyuki
Abstract: Background and aims: Thrombin, the active enzyme of the coagulation system, plays a critical role in the pathogenesis of atherosclerosis. Vascular repair promoted by stromal cell-derived factor-1 is a protective process in atherosclerosis. Consumption of low amount of alcohol is believed to reduce the risk of atherosclerotic cardiovascular disease but the mechanism is unclear. This study evaluated whether alcohol can modulate the expression of stromal cell-derived factor-1 and the pro-atherosclerotic activity of thrombin. Methods: Hepatocytes, monocytes, vascular endothelial and vascular smooth muscle cells were pre-treated with increasing concentrations of ethanol before stimulation with thrombin. The expression of cytokines, chemokines, cell adhesion molecules and epigenetic factors, including histone deacetylases and sirtuins, was evaluated. Results: Thrombin stimulation significantly enhanced the expression of pro-inflammatory cytokines, chemokines and cell adhesion molecules, but significantly decreased the expression of stromal cell-derived factor-1. Pre-treatment of cells with a low dose of ethanol significantly decreased thrombin-induced production of pro-inflammatory cytokines and chemokines, and significantly increased the production of stromal cell-derived factor-1 compared to cells treated with thrombin alone. Ethanol significantly counteracted the decreased expression of histone deacetylases and sirtuins induced by thrombin. Inhibition of histone deacetylase-2 with trichostatin A or with specific siRNA abolished the stimulatory activity of low-dose ethanol on stromal cell-derived factor-1. Conclusions: Low-dose of ethanol attenuates the inflammatory response and counteracts the reduced expression of stromal cell-derived factor-1 induced by thrombin via an epigenetic mechanism, providing a potential explanation for the protective activity of low dose of alcohol in atherosclerosis. Highlights: Thrombin plays a key role in the pathogenesis of cardiovascular diseases. Stromal cell-derived factor-1 (SDF-1) may protect vessels by promoting reparative processes. Previous studies have linked low alcohol intake with less frequent vascular events. Thrombin decreases SDF-1 expression in vascular cells. Low doses of alcohol block thrombin-mediated low SDF-1 expression by regulating epigenetic factors.